2010
DOI: 10.1162/jocn.2009.21272
|View full text |Cite
|
Sign up to set email alerts
|

Training the Brain to Weight Speech Cues Differently: A Study of Finnish Second-language Users of English

Abstract: Foreign-language learning is a prime example of a task that entails perceptual learning. The correct comprehension of foreign-language speech requires the correct recognition of speech sounds. The most difficult speech-sound contrasts for foreign-language learners often are the ones that have multiple phonetic cues, especially if the cues are weighted differently in the foreign and native languages. The present study aimed to determine whether non-native-like cue weighting could be changed by using phonetic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 49 publications
3
94
1
Order By: Relevance
“…It was initially designed to train phonetic discrimination in Japanese speakers of English, but later has been extended to other language groups as well. High variability phonetic training has proven to be a very successful, theoretically well-grounded and popular technique for speech training (see Bradlow et al 1997Bradlow et al , 1999Giannakopoulou, Uther, and Ylinen 2013;Iverson, Hazan, and Bannister 2005;Iverson and Evans 2009;Lively, Logan, and Pisoni 1993;Lively et al 1994;Uther et al 2007;Ylinen et al 2010) and is the technique behind one of the mobile device applications studied in this research project (the UCL Vowel Trainer).…”
Section: Introductionmentioning
confidence: 99%
“…It was initially designed to train phonetic discrimination in Japanese speakers of English, but later has been extended to other language groups as well. High variability phonetic training has proven to be a very successful, theoretically well-grounded and popular technique for speech training (see Bradlow et al 1997Bradlow et al , 1999Giannakopoulou, Uther, and Ylinen 2013;Iverson, Hazan, and Bannister 2005;Iverson and Evans 2009;Lively, Logan, and Pisoni 1993;Lively et al 1994;Uther et al 2007;Ylinen et al 2010) and is the technique behind one of the mobile device applications studied in this research project (the UCL Vowel Trainer).…”
Section: Introductionmentioning
confidence: 99%
“…Speaking a language other than the native one requires the speaker to adapt to different speech sounds and prosodic systems and to the vocal ideals of other cultures [1]. Contrastive research in language learners' production and perception of a foreign language has to a large extent focused on the accuracy of performance in the target language or the influence of the native language on the target language [for examples, see [2,3,4,5]; for examples of differences between Finnish and English, see [6,7,8]]. Voice parameters are prone to be affected by a language change between native and foreign languages.…”
Section: Introductionmentioning
confidence: 99%
“…In Finnish intonation, the highest peak in the F0 contour is typically located at the start of a sentence and the end of the sentence is low. Also, the intonation range is narrower in Finnish than in English [6,30,31,32]. …”
Section: Introductionmentioning
confidence: 99%
“…Peltola et al (2014) showed that university English students produced English vowels in a more native-like manner after explicit pronunciation teaching and the learning effect was best reflected in /ɪ/. A study by Ylinen et al (2010) has also provided evidence that native Finnish speakers tend to use duration cues rather than spectral cues in the discrimination of the English /i:/ -/ɪ/ contrast, which can also be expected to be reflected in the production of these vowels. Looking at the results of the present study, it seems that the control group assimilated the English lax /ɪ/ to Finnish /i/ category and produced it as more frontal than the early learners, resulting in higher F2 values.…”
Section: Discussionmentioning
confidence: 99%